Effectiveness of museum visits: attitude and learning of history - Sahani, Chatterjee; Prakasha, G. S. (International Journal of Evaluation and Research in Education (IJERE), 2024)
This quasi-experimental study investigates the effectiveness of museum visit on 6th-grade students’ attitude towards and learning of history. The study engaged 120 students in the museum visit intervention. That includes, 60 students in the experimental group and 60 students in the control group. The study design included pre-test and post-test measures. The study administered an achievement test and an attitude scale toward history. The study analyzed the data using the repeated measures analysis of variance (ANOVA) statistical test. The study’s result revealed that the experimental group outperformed the control group in achievement test scores of histories. The museum-visit group expressed a more positive attitude towards history learning and engagement. These findings underscore museums’ potential as experiential learning environment, offering knowledge and fostering a positive attitude towards history. The study recommends the future researchers to conduct similar empirical studies in science subjects as a venue for place-based pedagogy in the Indian context.